PROPOSED PERFORMANCE APPRAISAL SYSTEM INNOVATION USING BALANCED SCORECARD METHOD FOR PT JATI MIARA KASAE (ARCANA INDONESIA) - Ainun Adhelia Fitri (Cerdika: Jurnal Ilmiah Indonesia, 2025)
The event organizer industry, such as Arcana Indonesia in Bandung, faces major challenges related to flexibility and irregular working hours, resulting in high overtime and employee turnover; in the past three months, nine employees have resigned, causing material and non-material losses to the company. This research aims to analyze existing performance appraisal methods, identify the causes of turnover, and design a Balanced Scorecard (BSC)-based performance appraisal system, which was chosen for its comprehensive approach in measuring organizational success from various aspects. Qualitative methods were used with data collection through interviews and internal document analysis, which showed that Arcana Indonesia did not have a structured performance appraisal system. Other causes of turnover included lack of structure and clear expectations, unconstructive feedback, high workload, and unclear career paths. Based on these findings, BSC set goals from the Internal Process, Financial, Customer, and Learning & Growth perspectives to address these issues, such as increased freelancer utilization, improved profit margins, additional B2B clients, and achievement of employee satisfaction and reduced turnover.